Trauma in the childhood stories of people who have injected drugs. (3rd March 2016) - Hammersley, Richard; Dalgarno, Phil; McCollum, Sean; Reid, Marie; Strike, Yvonne; Smith, Austin; Wallace, Jason; Smart, Audrey; Jack, Moria; Thompson, Alan; Liddell, David
Abstract: Aim : To document childhood trauma in the life stories of people who have injected drugs. Method : Fifty-five participants (38 m, 17 f) recruited via Scottish recovery networks, who had injected drugs in the previous five years, were interviewed by peer researchers using the Life Story method. Results : Remembered childhood trauma included persistent violence, repeated sexual abuse, neglect and traumatic bereavements. Many traumas were related to adult alcohol use. Few participants told of no trauma, some of severe trauma contributing to subsequent drug problems, some recounted stories including traumatic events, but not linked to later drug problems. A few told of initial severe behavioural problems leading to trauma for the child and to drug problems. Drug problems followed trauma by various routes, without straightforward cause and effect: direct use of drugs as avoidant coping; juvenile heavy recreational use that escalated; forming relationships in mid to late teens with criminals. For men, this involved enmeshment in drug dealing, crime and prison. Some women formed relationships with men who injected drugs, who often introduced them to drugs, and some of whom were violently abusive. Heroin injecting was an effective means of blotting out distressing thoughts and feelings. Although, childhood stories also contained positive memories, factors that might have promoted resilience were rarely mentioned. Conclusions : Severe childhood trauma was common and gravitated people towards problem drug use via various pathways. Participants had often normalised the problems and did not remember adult help. Parental alcohol use contributed to trauma. Addiction services need to be more trauma minded.